2016
DOI: 10.1017/rdc.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

A Marine Reservoir Effect ∆R Value for Kitandach, in Prince Rupert Harbour, British Columbia, Canada

Abstract: ABSTRACT. Prince Rupert Harbour (PRH), on the north Pacific Coast of British Columbia, contains at least 157 shell middens, of which 66 are known villages, in an area of approximately 180 km 2 . These sites span the last 9500 yr and in some cases are immense, exceeding 20,000 m 2 surface area and several meters in depth. Recent archaeological research in PRH has become increasingly reliant on radiocarbon dates from marine shell for developing chronologies. However, this is problematic as the local marine reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Early archaeological efforts, published before the first marine calibration curve, Marine98 (Stuiver et al 1998), employed the second approach (Archer 1992; Moss and Erlandson 1992; Southon et al 1990), generating ΔR estimates ranging from 245 to 430 years, with estimated errors of ±50–100 years. More recent work has relied on regional estimates (Ames 2005; Cybulski 2016; McLaren 2008) or employed the third approach (Edinborough et al 2016; Eldridge et al 2014; Martindale et al 2009; McKechnie and Eldridge 2013).…”
Section: Calculating δRmentioning
confidence: 99%
See 2 more Smart Citations
“…Early archaeological efforts, published before the first marine calibration curve, Marine98 (Stuiver et al 1998), employed the second approach (Archer 1992; Moss and Erlandson 1992; Southon et al 1990), generating ΔR estimates ranging from 245 to 430 years, with estimated errors of ±50–100 years. More recent work has relied on regional estimates (Ames 2005; Cybulski 2016; McLaren 2008) or employed the third approach (Edinborough et al 2016; Eldridge et al 2014; Martindale et al 2009; McKechnie and Eldridge 2013).…”
Section: Calculating δRmentioning
confidence: 99%
“…Most presented ΔR as a constant, but some (Eldridge et al 2014; McKechnie and Eldridge 2013; Southon and Fedje 2003) presented evidence of changes over time. Our settlement history research (see Ames and Martindale 2014; Letham et al 2015; Martindale, Letham, et al 2017; Martindale, Marsden, et al 2017) relies heavily on the dating of shell samples; thus we developed a ΔR test in concert with the Scottish Universities Environmental Research Centre to apply the approach of Russell and colleagues (2011) to the PRH, which produced a statistically robust result spanning the last 5,000 years (Edinborough et al 2016). Here we consider this result in comparison to both (1) the history of ΔR estimates in the PRH region and (2) commonly applied but inaccurate and imprecise calculations illustrated with our data.…”
Section: The Prince Rupert Harbour Examplementioning
confidence: 99%
See 1 more Smart Citation
“…All dates are of terrestrial origin and there are no issues with a marine reservoir effect (c.f. Edinborough et al, 2016Edinborough et al, , 2017. The majority of dates are collected from published literature and excavation reports but some are unpublished.…”
Section: Radiocarbon Dates and Summed Radiocarbon Probability Distribmentioning
confidence: 99%
“…Although Dewar et al (2012) provide the necessary data to correct the carbon reservoir effect of seawater in this area, the assumption that the reservoir effect remained stable during the millennium of occupation at KBB needs to be tested in the future with a paired-sample approach (e.g. Edinborough et al 2016). Such a test is beyond the scope of this study, and, for now, we assume that the weighted mean reported by Dewar et al (2012) ( R=146±85) provides an adequate correction of the calibrated marine shell dates from KBB.…”
Section: Researchmentioning
confidence: 99%